2022
DOI: 10.1177/09612033221093508
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic manifestations of juvenile systemic lupus erythematosus: An emphasis on anemia

Abstract: Objective Anemia is common in patients with juvenile systemic lupus erythematosus (jSLE). While autoimmune hemolytic anemia (AIHA) is the only etiology included in the classification criteria, the etiology of anemia in jSLE may be diverse. We aimed to investigate the etiology of anemia in jSLE and the relationship between anemia and disease characteristics at onset and during the follow-up period. Methods Patients diagnosed with jSLE who met the Systemic Lupus Erythematosus International Collaborating Clinics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The intricate connection between nutrition and immunity is evident, especially in intensive care units, 4 and is crucial in infectious diseases and chronic illnesses. Micronutritional deficiencies are known to drive inflammation and are associated with increased morbidity and mortality 5–7 in various diseases including congestive heart failure, 8–10 chronic kidney diseases 11–13 autoimmune thyroid diseases, 14–18 inflammatory bowel disease, 19,20 cancer, 21–23 atopic diseases 24,25 and even in obesity 26–29 …”
Section: Introductionmentioning
confidence: 99%
“…The intricate connection between nutrition and immunity is evident, especially in intensive care units, 4 and is crucial in infectious diseases and chronic illnesses. Micronutritional deficiencies are known to drive inflammation and are associated with increased morbidity and mortality 5–7 in various diseases including congestive heart failure, 8–10 chronic kidney diseases 11–13 autoimmune thyroid diseases, 14–18 inflammatory bowel disease, 19,20 cancer, 21–23 atopic diseases 24,25 and even in obesity 26–29 …”
Section: Introductionmentioning
confidence: 99%
“…The significance of the complement status in hematological involvement of patients with juvenile onset SLE was previously reported and shown that low complement C3 was associated with hematological involvement and low complement C4 was more frequently encountered in patients with anemia. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the complement status in hematological involvement of patients with juvenile onset SLE was previously reported and shown that low complement C3 was associated with hematological involvement and low complement C4 was more frequently encountered in patients with anemia. 22,23 Complement activation is generated by 3 main pathways. Classical pathway activation is a well known and main pathway involving in the SLE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…By degrading ferroportin, which enables exporting iron into circulation, hepcidin decreases iron absorption from the gastrointestinal tract and decreases the accessibility of iron stored in macrophages. The blocking of iron absorption and mobilization is a critical clinical finding, which is associated with a worsened prognosis and outcome in chronic diseases such as congestive heart failure (30,31), chronic kidney diseases (32-34) (NCT03029208, NCT02940860, and NCT01864161), autoimmune diseases (35)(36)(37)(38)(39), inflammatory bowel disease (40,41), cancer (42)(43)(44), atopic diseases (45,46) (NCT03815981 and NCT03816800), and even in obesity (47-50) (NCT00030238). Importantly, in iron-deficient children who are not anemic, inflammation is a common finding (51).…”
Section: Iron Uptake Under Inflammation: a Real Problemmentioning
confidence: 99%